(untitled) (Journal of Guidance and Counselling Studies, 2023)
This study sought to determine the relationship between study habits and academic achievement among secondary school students in Anambra state. Four research questions and two null hypotheses guided the study. The design for this study was correlation design. The population of the study comprise 23,396 students in 257 public secondary schools in Anambra State. The sample for the study consists of 1080 students. The instruments for the study consist of two questionnaires, namely Study Habits Questionnaire (SHQ) and Academic Achievement Test in English Language (AATEL) both were adopted by the researcher. The instruments: Study Habits Questionnaire (SHQ) was validated in Nigeria by Osita in 2013 and Academic Achievement Test in English Language (AATEL) was also validated in Nigeria by the subject teacher. Study Habits Questionnaire (SHQ) has a reliability of 0.72 which was established by Osita in 2013 using Cronbach alpha reliability in a pilot test. The administration of the instruments was done through direct delivery approach by this method; copies of the questionnaires were distributed personally to the respondents with the help of six research assistants. The data collected were scored and analyzed. Research question 1 and 2 was analyzed using Mean and frequency table. The t-test of correlation was used test the two null hypotheses at P<0.05 level of significance. The major findings of the study show that there exist a medium moderate positive relationship between study habit of male and female students and their academic achievement in English Language in Anambra state, there is a significant relationship between study habits and academic achievement in English Language in Anambra state. Recommendations were made that, the guidance unit in secondary schools should organize study habits training for their students often. This can be at the beginning of every term or twice in a year or session especially for the new and old students. This will help them acquire the rightful study skills they need as they progress to further classes, therefore enabling them perform better in their academic pursuit. Also, Counsellors, Teachers, Parents, and authorities of public schools should both individually and collectively assist the students towards acquiring good study skills to improve their academic achievement.